Will it float? The New Keynesian Phillips curve tested on OECD panel data - Roger Bjørnstad; Ragnar Nymoen (Statistics Norway, Research Department, 2006)
Galí, Gertler and Lòpez-Salido (2005), GGL, assert that the hybrid New Keynesian Phillips curve, NPC, is robust to different choices of estimation procedure and so some forms of specification bias. Specifically, the dominance of forward-looking behavior is robust according to GGL. We assess the NPC on a panel data set from OECD countries and find that the forward rate of inflation dominates also on the panel data set. However, when variables consistent with alternative inflation models are introduced in the models, the forward term is no longer significant. Such an outcome is predicted by the incomplete competition model of inflation, ICM, meaning that the ICM encompasses the NPC. The opposite does not apply. The non-robustness of the OECD panel data NPC is in alignment with a previous encompassing test on euro-area data, as well as tests on data from the UK and from Norway. GGL on their part do not test the robustness of the NPC features with respect to existing inflation models.
Keywords: C23; C52; E12; E31; 330; New Keynesian Phillips Curve; forward looking price setting; panel data model; encompassing